DIGITAL TRANSFORMATION, ARTIFICIAL INTELLIGENCE, CLIMATE CRISIS, MIGRATION: CURRENT ISSUES AND TRENDS (Universal International Scientific Journal, 2026)
This article analyzes current global trends that are affecting the development of modern society and the economy - digital transformation, artificial intelligence, climate crisis - as well as migration processes. -The economic consequences are considered.
Keywords: digital transformation; artificial intelligence; climate crisis